Pengaruh Penggunaan Debu Basalt pada Lahan Tanah Sub Optimal terhadap Perubahan pH Tanah - Yusup Hendronursito; J Barus; Kusno Isnugroho; DC Birawidha; M Amin (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Hendronursito Y, Barus J, Isnugroho K, Birawidha DC, Amin M, Muttaqii MA. 2019. the effect of used of basalt powder for sub optimum soil toward pH soil changes. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 178-185. Palembang: Unsri Press. A The use of basalt dust as a stone meal in Indonesia is still rarely found, while basalt has enormous potential as a fertilizer that is rich in micro and macro nutrients needed by plants especially in the treatment of soil amelioration. Development of complete organic fertilizer enriched with minerals is also very necessary. This study aims to determine the potential of basalt dust on soil ameliorants to changes in acidic soil pH in sub-optimal land. The experiments is carried out on the soil which is given basalt dust treatment in a test column with incubation treatment on a pot. Design experiments uses the orthogonal array L16 taguchi, with parameters of the percentage of basalt weight of organic fertilizer (A) 0, 10, 30, and 60%, the weight of organic fertilizer as much as (B) 5, 20, 35, and 50 tons/ha, and high water immersion (C) 100 and 300 mm. Experiments were carried out on soils treated with basalt dust in a test column with incubation treatment for 3 months and then the change in pH was measured using a pH meter PHT-027. Based on ANOVA analysis it is known that the weight percentage of basalt powder has the most significant effect on changes of soil pH. While the amount of water soaking have less significant effect on changes of soil pH. To obtain the optimum pH change can be used 60% basalt mixture by organic fertilizer, application of fertilizer are 20 tons/ha, and watering 100 mm.Keywords: anova, basalt, micronutrient dan macronutrient, taguchi